EXPLORING THE INNOVATIVE APPROACH OF TEACHING AND LEARNING FOR TERTIARY EDUCATION – IN THE FIELD STUDY OF ACCOUNTING - Tchiang, Van Kam (PEOPLE: International Journal of Social Sciences, 2024)
Innovative approaches to teaching and learning have become indispensable in recent years, and the field of accounting is no exception. The use of various innovative approaches such as the crowdsourcing model, active learning, formative assessment, gamification, and active use of technology are examples of innovative pedagogies that can transform teaching and learning for tertiary education. These pedagogies can target skills that most impact students’ career prospects and social lives, and secure the necessary depth and breadth of skills needed for lifelong learning. This research aims to explore the effectiveness of innovative pedagogies in teaching accounting. The study will involve interviews and surveys of accounting students to gather their perspectives on how innovative approaches impact their learning process. The research will investigate how innovative pedagogies can improve student engagement, enhance motivation, increase capacity for critical thinking skills, provide personalized adaptive learning processes, and foster learning development through collaboration. In summary, this research seeks to contribute to the growing body of literature on innovative pedagogies in accounting education. By exploring the effectiveness of innovative approaches, this study aims to provide insights into how accounting educators can improve their teaching practices and better prepare students for the demands of the modern human resource market on novice accountants.